Freshly-mixed and setting calcium-silicate cements stimulate human dental pulp cells. Issue 5 (May 2018) - Pedano, Mariano S.; Li, Xin; Li, Shuchen; Sun, Zeyi; Cokic, Stevan M.; Putzeys, Eveline; Yoshihara, Kumiko; Yoshida, Yashuhiro; Chen, Zhi; Van Landuyt, Kirsten; Van Meerbeek, Bart
Graphical abstract: Highlights: A novel approach to test hydraulic calcium-silicate cements (hCSCs) is proposed. 'Freshly-mixed and setting' hCSCs are suitable for in vitro bioactivity assays. A new phosphopullulan-based hCSC stimulates human dental pulp cells. Abstract: Objectives: To evaluate the effect of the eluates from 3 freshly-mixed and setting hydraulic calcium-silicate cements (hCSCs) on human dental pulp cells (HDPCs) and to examine the effect of a newly developed hCSC containing phosphopullulan (PPL) on HDPCs. Methods: Human dental pulp cells, previously characterized as mesenchymal stem cells, were used. To collect the eluates, disks occupying the whole surface of a 12-well plate were prepared using an experimental hCSC containing phosphopullulan (GC), Nex-Cem MTA (GC), Biodentine (Septodont) or a zinc-oxide (ZnO) eugenol cement (material-related negative control). Immediately after preparing the disks (non-set), 3 ml of Dulbecco's Modified Eagle Medium (DMEM) with 10% fetal bovine serum (FBS) were added. The medium was left in contact with the disks for 24 h before being collected. Four different dilutions were prepared (100%, 50%, 25% and 10%) and cell-cytotoxicity, cell-proliferation, cell-migration and odontogenic differentiation were tested. The cell-cytotoxicity and cell-proliferation assays were performed by XTT-colorimetric assay at different time points. The cell-migration ability was tested with the wound-healing assay and the odontogenic differentiation capacity of hCSCs on HDPCs was tested with RT-PCR. Results: Considering all experimental data together, the eluates from 3 freshly-mixed and setting hCSCs appeared not cytotoxic toward HDPCs. Moreover, all three cements stimulated proliferation, migration and odontogenic differentiation of HDPCs. Significance: The use of freshly-mixed and setting hCSCs is an appropriate approach to test the effect of the materials on human dental pulp cells. The experimental material containing PPL is non-cytotoxic and positively stimulates HDPCs.